Pendampingan Belajar Matematika Berbantuan Media Pembelajaran Berbasis Game Counting Bunny untuk Peserta Bimbel di Rumah Belajar Matematika - Arini Hidayati; Nur Azizah; Maimuna Maimuna; Deni Ihya Ulumuddin; Ummi Nur Aisyah (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
Rumah Belajar Matematika is a tutoring place located in Kebonan Hamlet, Yosowilangun Kidul Village, Yosowilangun District, Lumajang Regency, East Java. The tutoring participants are elementary and junior high school students, totaling 15 people. Based on the results of observations made by the KKN team, so far the tutors at the Mathematics Learning House have never made learning innovations, especially in the use of game-based learning media. This makes us compelled to carry out mentoring activities in learning mathematics by utilizing learning media based on the counting bunny game which can make it easier for students to understand the concepts of addition and multiplication of integers. The expected goals of this service activity include: 1) so that mathematics learning activities in the tutoring can be more attractive, interesting, and fun, so that tutoring participants can be more enthusiastic in learning mathematics; 2) encourage teachers or tutors in tutoring places to be able to innovate more in learning activities, one of which is the use of learning media; 3) the use of learning media is expected to help make it easier for tutors to convey mathematical material or concepts; 4) students find it easier to understand the material or concepts presented; and 5) student learning outcomes are getting better. This learning mentoring activity was carried out for 2 days, where the KKN team acted as tutors. At the end of the activity, a response questionnaire was given to the tutoring participants to find out their response to the learning process using the counting bunny game, including enthusiasm, motivation, and interest. The results of the participants' responses showed positive results, with an average score of 3.35 and included in the high category, which means that the participants felt more enthusiastic, motivated, more interested in learning mathematics after using the counting bunny game learning media.